Chromosomal characterization of two medicinal plants from Bangladesh (Journal of Bangladesh Academy of Sciences, 2024)
Two medicinal plants, O. corniculata and O. triangularis, were investigated cytogenetically for proper characterization. Both plants had Complex Chromocenter interphase nuclei and Continuous prophase chromosomes. O. corniculata was discovered to have 2n=48 chromosomes and 2n=30 in O. triangularis. The chromosomal length range was 0.82±0.02-1.61±0.02 in O. corniculata and 1.02±0.02- 2.52±0.03 in O. triangularis. The total length of the 2n chromosome complement was 53.52±1.19 and 46.76±0.41 for O. corniculate and O. triangular, respectively. The two species differed in centromeric formulas, such as 48m for O. corniculata and 28m+2sm for O. triangularis. In their karyotype, no steady decrease in chromosomal length was seen. These characteristics showed that O. corniculata and O. triangularis could be considered primitive species. Therefore, compiling the cytogenetic features will be helpful to ensure the genuine identification and characterization of the two medicinally important Oxalis species.J. Bangladesh Acad. Sci. 48(1); 135-140: June 2024